2009
DOI: 10.1111/j.1540-8159.2009.02465.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation at Growing Myocardium: No Evidence of Coronary Artery Obstruction or Intimal Plaque Formation Early and Late after Energy Application

Abstract: By means of the present study, we did not observe any affection of the coronary arteries after cryoenergy application at growing myocardium in young piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
1
24
3
4
Order By: Relevance
“…In contrast, in a previous study of our group using the same piglet model, single cryoenergy application had not resulted in coronary artery wall changes as documented by angiography, ICUS and histology . It is of note, however, that after RFA in the same animal model, leukocyte infiltration of the layers of the RCA was found in 3/5 animals studied at the same time …”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In contrast, in a previous study of our group using the same piglet model, single cryoenergy application had not resulted in coronary artery wall changes as documented by angiography, ICUS and histology . It is of note, however, that after RFA in the same animal model, leukocyte infiltration of the layers of the RCA was found in 3/5 animals studied at the same time …”
Section: Discussioncontrasting
confidence: 82%
“…Cryothermy has emerged as an alternative energy source with an improved safety profile for treatment of SVT in children. As of yet, neither persistent complete atrioventricular (AV) block nor significant coronary artery obstruction have been reported clinically or in animal models . The relatively smaller experience with cryoablation may be an important reason that rare adverse events have not been identified to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding, which was also confirmed by Kriebel et al, 12 can provide some comfort to the physician, since most ablations at every age are performed for AV groove related substrates (71% in infants and 89% in children). 13 Saul et al 2 suggested that transmurality of the lesions may have been a factor in lesion expansion.…”
Section: Important Observations From This Studysupporting
confidence: 74%
“…However, 2 prior studies did demonstrate that CRYO can have minimal effects on nearby coronary arteries of infant pigs, with increased mural echogenicity by intracoronary ultrasound in 1 of 5 animals, and some lesion extension into the medial coronary wall of the left circumflex, without stenosis or flow abnormalities. 12,14,15 These changes were far less than those observed with RF lesions in prior studies. 16 …”
Section: Important Observations From This Studycontrasting
confidence: 38%